Data Access Layer: A Programming Paradigm on Cloud - Guleria, Pratiyush (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Database is important for any application and critical part of private and public cloud platforms. For compatibility with cloud computing we can follow architectures like three tier architecture in .Net Technologies such that database layer should be separate from user and business logic layers. There are some other issues like following ACID properties in databases, providing dynamic scalability by using Shared-disk Architecture and efficient multi-tenancy, elastic scalability, and database privacy.